Psychometric validation of the Clubhouse climate questionnaire as an autonomy support measure for people with severe mental illness. (February 2015) - Fitzgerald, Sandra; Umucu, Emre; Arora, Simran; Huck, Garrett; Benton, Susan Flowers; Chan, Fong
Abstract Background: Self-determination represents a paradigm shift from "shoulds" to "decisions and behaviors" as the best options for helping people with mental illness achieving recovery goals. Autonomy support plays an important role in self-determination. Aims: The purpose of this study was to validate the Clubhouse climate questionnaire (CCQ) as an autonomy support measure. Method: One hundred and twenty-four participants were recruited from eight Clubhouse programs in Hawaii. Measurement structure of the CCQ was evaluated using exploratory and confirmatory factor analysis. Findings: CCQ is a unidimensional scale with good reliability and acceptable levels of divergent and convergent validity. Conclusions: CCQ is a brief, reliable and valid instrument for assessing autonomy support and contributes to the use of self-determination as a paradigm for improving recovery outcomes in psychiatric rehabilitation.